SOSIALISASI DAMPAK PENGGUNAAN GADGET PADA SISWA KELAS V DI SD SAINS ISLAM AL-FARABI - Juwanda Prayuda; Aiman Faiz; Isma Hanifatul Salma; Laila Nurul Robbiah; Lelik Khoeroyaroh; Lena Marlina (SIKAP : Jurnal Sinar Inovasi Kajian Pemberdayaan Masyarakat, 2025)
The aim of this Community Service activity in the School Environment is to provide insight and knowledge about the dangerous impacts of gadgets if you are not wise in using gadgets. This service needs to be done because there is a gap between age and technology so this is important to anticipate bad things that will happen to students. Then at the same time coaching students to reduce playing with gadgets. For this reason, this service also involves teachers. On this occasion, a pre-test (before) and post-test (after) this service can be carried out so that the extent to which we understand the impact of gadgets can be clearly measured. The service steps consist of the preparation stage, activity implementation stage, and evaluation stage. This service was carried out on March 25 2024, attended by 112 students and 6 teachers at SDSI Al-Farabi. So, from the results of the pre-test and post-test, there is an increase in understanding and new insights regarding the impact of gadgets on students and the final result is that students want to reduce playing with gadgets.